Kajian Alternatif Metode Kerja Perbaikan Trashrack (Saringan) Intake Malalo Unit PLTA Singkarak - Kurniawan, Elfin; Simaremare, Arionmaro Asi; Prahastono, Iswan; Nainggolan, Akiman (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2021)
The Singkarak Hydroelectric Power Plant with a capacity of 175MW is the backbone of the Central Sumatra Subsystem (SumBagTeng) in the Sumatran electricity interconnection system so that the reliability of the Singkarak hydropower operation must be maintained. However, after more than 12 years of operation the Singkarak Hydroelectric Power Plant suffered damage to the trash rack of the Malalo Intake caused by the September 30, 2009 earthquake that hit Padang-Pariaman where the filter segments and the filter girder beam fell to the bottom of the intake. This results in waste originating from Singkarak lake being free to enter the head race tunnel and then to the generator engine generator which can interfere with the operation of the Singkarak hydropower plant so it is necessary to repair the Malalo trashrack intake.This study aims to evaluate several alternative work methods for repairing the trash-rack intake of Malalo PLTA Singkarak to minimize disruption to the operation of PLTA Singkarak during repairs. Three alternative improvement methods were evaluated using the Zero-One technique and weighting. From the results of the evaluation, it was found that the underwater construction work method is the best alternative to repair among other methods. Furthermore, the details of the implementation plan for the underwater construction work method are presented as a reference for the implementation of the repair PLTA Singkarak trash rack.